A ferroelectric depolarization field enhanced multi-junction photovoltaic device and a method of making the same
Patent Information
- Application Number
- CN202311472717.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-07
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-07
AI Technical Summary
一般而言,Ga2O3基自驱动光电探测器往往通过器件内部异质结内建电场或者肖特基结界面处内建电场来分离光生载流子,其光生载流子分离能力很有限,导致当前Ga2O3基自驱动深紫外光电探测器的探测率(响应度)无法满足实际应用需求
[0036]本发明的铁电退极化场增强多结光伏型器件,具体为铁电退极化场增强BFMO/n-Ga2O3/ZnO多结光伏型自驱动深紫外光电探测器,包括BFMO铁电薄膜层,BFMO是一种无铅铁电材料,具有自发极化特性和非常好的铁电特性(Pr>60μC/cm2);BFMO与n-Ga2O3接触形成异质结;n-Ga2O3与ZnO接触形成异质结。由于n-Ga2O3、BFMO、ZnO三者能带结构的良好匹配,n-Ga2O3/ZnO和n-Ga2O3/BFMO异质结界面处的内建电场具有相同的方向。通过调控BFMO中的铁电退极化电场方向与BFMO/n-Ga2O3异质结、n-Ga2O3/ZnO异质结界面处内建电场方向一致,使三个同方向电场共同分离光生载流子,从而实现器件性能的提升。
Smart Images

Figure CN117613130B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of optoelectronic device technology, and in particular to a ferroelectric depolarization field-enhanced multijunction photovoltaic device and its fabrication method. Background Technology
[0002] Photovoltaic devices mainly include solar cells and self-powered photodetectors. Among them, photovoltaic self-powered photodetectors can achieve photoelectric detection without relying on an external power source, possessing advantages such as high sensitivity, small size, easy integration, and low energy consumption, making them a current research hotspot in the field of photoelectric detection. In particular, photovoltaic self-powered deep ultraviolet photodetectors have outstanding advantages such as strong anti-interference ability and high sensitivity, showing broad application prospects in fields such as fire monitoring, missile early warning, and biological analysis. The novel semiconductor material gallium oxide (Ga2O3) has an ultra-wide direct bandgap (4.8–4.9 eV) and excellent thermal and chemical stability, making it one of the most promising materials for fabricating deep ultraviolet photodetectors. Generally, Ga2O3-based self-powered photodetectors often separate photogenerated carriers through the built-in electric field of the heterojunction or the built-in electric field at the Schottky junction interface. However, its photogenerated carrier separation capability is very limited, resulting in the detectivity (responsivity) of current Ga2O3-based self-powered deep ultraviolet photodetectors failing to meet practical application requirements.
[0003] Given the current shortcomings of Ga2O3-based self-driven deep ultraviolet photodetectors, it is necessary to improve them. Summary of the Invention
[0004] In view of this, the present invention proposes a ferroelectric depolarization field enhanced multijunction photovoltaic device and its fabrication method to solve the technical problems existing in the prior art.
[0005] In a first aspect, the present invention provides a ferroelectric depolarization field-enhanced multijunction photovoltaic device, comprising:
[0006] Substrate;
[0007] BiFe 1-x Mn x An O3 ferroelectric thin film layer is located on the surface of the substrate, wherein 1% ≤ x ≤ 5%;
[0008] n-Ga2O3 thin film layer, located in the BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer away from the substrate;
[0009] A ZnO thin film layer is located on the surface of the n-Ga2O3 thin film layer on the side away from the substrate;
[0010] The top electrode is located on the surface of the ZnO thin film layer away from the substrate.
[0011] Preferably, in the ferroelectric depolarization field-enhanced multijunction photovoltaic device, the n-type doping element in the n-Ga2O3 thin film layer includes at least one of Si, Ge, and Sn;
[0012] The molar fraction of n-type dopant elements in the n-Ga2O3 thin film layer is 0.1% to 3%.
[0013] Preferably, in the ferroelectric depolarization field-enhanced multijunction photovoltaic device, the top electrode includes any one of Ag electrode, Au electrode, In electrode, and ITO electrode.
[0014] Preferably, in the ferroelectric depolarization field-enhanced multijunction photovoltaic device, the substrate includes either an FTO conductive glass substrate or an ITO conductive glass substrate.
[0015] Preferably, in the ferroelectric depolarization field-enhanced multi-junction photovoltaic device, the BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer is 80–400 nm;
[0016] And / or, the thickness of the n-Ga2O3 thin film layer is 120–300 nm;
[0017] And / or, the thickness of the ZnO thin film layer is 10–50 nm.
[0018] Secondly, the present invention also provides a method for fabricating the aforementioned ferroelectric depolarization field-enhanced multijunction photovoltaic device, comprising the following steps:
[0019] Provide substrate;
[0020] BiFe was prepared on the substrate surface 1-x Mn x O3 ferroelectric thin film layer;
[0021] In the BiFe 1-x Mn x An n-Ga2O3 thin film layer is prepared on the surface of the O3 ferroelectric thin film layer away from the substrate;
[0022] A ZnO thin film layer is prepared on the surface of the n-Ga2O3 thin film layer away from the substrate;
[0023] A top electrode is fabricated on the surface of the ZnO thin film layer away from the substrate.
[0024] Preferably, the fabrication method of the ferroelectric depolarization field-enhanced multijunction photovoltaic device employs pulsed laser deposition, magnetron sputtering, or sol-gel methods to prepare BiFe on the substrate surface. 1-x Mn xO3 ferroelectric thin film layer;
[0025] Atomic layer deposition, magnetron sputtering, pulsed laser deposition, or sol-gel method can be used to deposit BiFe 1- x Mn x n-Ga2O3 thin film layer is prepared on the surface of O3 ferroelectric thin film layer;
[0026] ZnO thin films were prepared on the surface of the n-Ga2O3 thin film using atomic layer deposition, magnetron sputtering, or pulsed laser deposition.
[0027] Top electrodes are prepared on the surface of the ZnO thin film using vacuum evaporation, magnetron sputtering, or electron beam deposition.
[0028] Preferably, the method for fabricating the ferroelectric depolarization field-enhanced multijunction photovoltaic device employs the sol-gel method to prepare BiFe 1-x Mn x The O3 ferroelectric thin film layer specifically includes the following steps:
[0029] Bismuth nitrate pentahydrate, ferric nitrate nonahydrate, and manganese acetate tetrahydrate were added to an organic solvent to obtain BiFe 1- x Mn x O3 precursor solution; wherein the organic solvent includes a mixture of glacial acetic acid and ethylene glycol methyl ether; the molar ratio of bismuth nitrate pentahydrate, ferric nitrate nonahydrate, and manganese acetate tetrahydrate is 1:(0.95~0.99):(0.01~0.05);
[0030] BiFe 1-x Mn x The O3 precursor solution was spin-coated onto the substrate, dried at 200–400 °C, and then annealed at 450–650 °C to obtain BiFe. 1-x Mn x O3 ferroelectric thin film layer.
[0031] Preferably, the method for fabricating the ferroelectric depolarization field-enhanced multijunction photovoltaic device uses pulsed laser deposition to prepare an n-Ga2O3 thin film layer, specifically including the following steps:
[0032] Using n-Ga2O3 ceramic as the target material, BiFe was prepared. 1-x Mn x The substrate for the O3 ferroelectric thin film was placed in the vacuum chamber of a pulsed laser deposition apparatus. The substrate temperature was controlled at 25–550 °C, the pulsed laser energy at 250–600 mJ, the oxygen pressure at 0–8 Pa, and the deposition time at 20–60 min. 1-x Mn xAn n-Ga2O3 thin film layer is formed by deposition on the surface of the O3 ferroelectric thin film layer.
[0033] Preferably, the method for fabricating the ferroelectric depolarization field-enhanced multijunction photovoltaic device uses pulsed laser deposition to prepare a ZnO thin film layer, specifically including the following steps:
[0034] Using ZnO ceramic as the target material, a substrate with an n-Ga2O3 thin film layer is placed in the vacuum chamber of a pulsed laser deposition equipment. The substrate temperature is controlled at 100–600℃, the pulsed laser energy is 150–600 mJ, the oxygen pressure is 0–8 Pa, and the deposition time is 5–15 min, so that a ZnO thin film layer is deposited on the surface of the n-Ga2O3 thin film layer.
[0035] The method for fabricating a ferroelectric depolarization field-enhanced multijunction photovoltaic device according to the present invention has the following advantages over the prior art:
[0036] The ferroelectric depolarization field-enhanced multijunction photovoltaic device of the present invention is specifically a ferroelectric depolarization field-enhanced BFMO / n-Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetector, comprising a BFMO ferroelectric thin film layer. BFMO is a lead-free ferroelectric material with spontaneous polarization characteristics and very good ferroelectric properties (P0). r >60μC / cm 2 BFMO forms a heterojunction with n-Ga2O3; n-Ga2O3 forms a heterojunction with ZnO. Due to the good matching of the band structures of n-Ga2O3, BFMO, and ZnO, the built-in electric fields at the interfaces of the n-Ga2O3 / ZnO and n-Ga2O3 / BFMO heterojunctions have the same direction. By adjusting the direction of the ferroelectric depolarization electric field in BFMO to be consistent with the direction of the built-in electric field at the interfaces of the BFMO / n-Ga2O3 and n-Ga2O3 / ZnO heterojunctions, the three unidirectional electric fields can jointly separate photogenerated carriers, thereby improving device performance. Attached Figure Description
[0037] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0038] Figure 1 This is a schematic diagram of the structure of the BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetector of the present invention;
[0039] Figure 2The photocurrent response spectra of the BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetectors prepared in Examples 1-5 under 275nm ultraviolet light illumination are shown.
[0040] Figure 3 The spectral responsivity curves of the BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetectors prepared in Examples 1-5 are shown.
[0041] Figure 4 Spectral detectivity curves of the BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetectors prepared in Examples 1-5;
[0042] Figure 5 The single-cycle It curve of the BFMO / Si:Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Example 3 under 260nm ultraviolet light irradiation;
[0043] Figure 6 The photocurrent response spectra of the BFMO / Si:Ga2O3 / ZnO multijunction self-driven deep ultraviolet photodetector prepared in Example 3 under different polarization states under 260nm ultraviolet light illumination are shown.
[0044] Figure 7 The spectral responsivity curves of the BFMO / Si:Ga2O3 / ZnO multijunction self-driven deep ultraviolet photodetector prepared in Example 3 under different polarization states are shown.
[0045] Figure 8 The single-cycle It curves are shown for the Si:Ga2O3-based self-driven deep ultraviolet photodetector prepared in Comparative Example 1 and the BFMO / Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Comparative Example 2.
[0046] Figure 9 The spectral responsivity curves are shown for the BFMO / Si:Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Example 3, the Si:Ga2O3-based self-driven deep ultraviolet photodetector prepared in Comparative Example 1, and the BFMO / Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Comparative Example 2. Detailed Implementation
[0047] The technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0048] This invention provides a ferroelectric depolarization field-enhanced multijunction photovoltaic device. Specifically, photovoltaic devices include photovoltaic solar cells, photovoltaic self-driven photodetectors, etc., while the device of this invention is a ferroelectric depolarization field-enhanced multijunction photovoltaic self-driven deep ultraviolet photodetector, such as... Figure 1 As shown, it includes:
[0049] Substrate 1;
[0050] BiFe 1-x Mn x O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) 2, located on the surface of substrate 1, wherein 1% ≤ x ≤ 5%;
[0051] n-Ga2O3 thin film layer 3, located in BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer 2 away from the substrate 1;
[0052] ZnO thin film layer 4 is located on the surface of n-Ga2O3 thin film layer 3 away from substrate 1;
[0053] Top electrode 5 is located on the surface of ZnO thin film layer 4 away from substrate 1.
[0054] It should be noted that the photovoltaic self-driven deep ultraviolet photodetector of the present invention includes a substrate 1 and BiFe₂O₃ layers sequentially grown on one side surface of the substrate 1. 1-x Mn x 2. O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) 3. n-Ga2O3 thin film layer 4. ZnO thin film layer 5. Top electrode; The detector of this invention is a ferroelectric depolarization field enhanced BFMO / n-Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector, wherein BiFe 1-x Mn x O3 ferroelectric thin film is a lead-free ferroelectric material with spontaneous polarization and excellent ferroelectric properties (P). r >60μC / cm 2BFMO forms a heterojunction with n-Ga2O3; n-Ga2O3 forms a heterojunction with ZnO. Due to the good matching of the band structures of n-Ga2O3, BFMO, and ZnO, the built-in electric fields at the interfaces of the n-Ga2O3 / ZnO and n-Ga2O3 / BFMO heterojunctions have the same direction. By adjusting the direction of the ferroelectric depolarization electric field in BFMO to be consistent with the direction of the built-in electric field at the interfaces of the BFMO / n-Ga2O3 and n-Ga2O3 / ZnO heterojunctions, the three unidirectional electric fields can jointly separate photogenerated carriers, thereby improving the device performance.
[0055] In some embodiments, BiFe 1-x Mn x In the O3 ferroelectric thin film layer 2, 1% ≤ x ≤ 5%, preferably, x = 5%, i.e., BiFe 1-x Mn x O3 has the chemical formula BiFe 0.95 Mn 0.05 O3.
[0056] BiFe 1-x Mn x An O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) 2 is located on the surface of substrate 1, wherein 1% ≤ x ≤ 5%.
[0057] In some embodiments, BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer 2 is 80–400 nm.
[0058] In some embodiments, the thickness of the n-Ga2O3 thin film layer 3 is 120–300 nm, preferably 200 nm.
[0059] In some embodiments, the n-type doping element in the n-Ga2O3 thin film layer 3 includes at least one of Si, Ge, and Sn.
[0060] In some embodiments, the molar fraction of n-type dopant elements in the n-Ga2O3 thin film layer 3 is 0.1% to 3%.
[0061] Specifically, in some embodiments, the n-Ga2O3 thin film layer 3 is a Si-doped n-Ga2O3 thin film layer, denoted as Si:Ga2O3 thin film layer.
[0062] In some embodiments, the thickness of the ZnO thin film layer 4 is 10–50 nm.
[0063] In some embodiments, substrate 1 includes either an FTO conductive glass substrate or an ITO conductive glass substrate.
[0064] Specifically, FTO conductive glass refers to fluorine-doped SnO2 conductive glass, and the thickness of substrate 1 is 1.0 to 2.5 mm.
[0065] In some embodiments, the top electrode 5 includes any one of an Ag electrode, an Au electrode, an ln electrode, and an ITO electrode.
[0066] Based on the same inventive concept, the present invention also provides a method for fabricating the above-mentioned multi-junction self-driven deep ultraviolet photodetector, comprising the following steps:
[0067] S1, Provide a substrate;
[0068] S2. Preparation of BiFe on the substrate surface 1-x Mn x O3 ferroelectric thin film layer;
[0069] S3, in BiFe 1-x Mn x An n-Ga2O3 thin film layer is prepared on the surface of the O3 ferroelectric thin film layer away from the substrate;
[0070] S4. Prepare a ZnO thin film layer on the surface of the n-Ga2O3 thin film layer away from the substrate;
[0071] S5. Prepare a top electrode on the surface of the ZnO thin film layer away from the substrate.
[0072] In some embodiments, BiFe is prepared on the substrate surface using pulsed laser deposition, magnetron sputtering, or sol-gel methods. 1-x Mn x O3 ferroelectric thin film layer.
[0073] In some embodiments, atomic layer deposition, magnetron sputtering, pulsed laser deposition, or sol-gel methods are used to deposit BiFe 1-x Mn x n-Ga2O3 thin film layer is prepared on the surface of O3 ferroelectric thin film layer.
[0074] In some embodiments, a ZnO thin film layer is prepared on the surface of an n-Ga2O3 thin film layer using atomic layer deposition, magnetron sputtering, or pulsed laser deposition.
[0075] In some embodiments, a top electrode is prepared on the surface of a ZnO thin film using vacuum evaporation, magnetron sputtering, or electron beam deposition.
[0076] In some embodiments, BiFe is prepared on the substrate surface. 1-x Mn x The process before preparing the O3 ferroelectric thin film layer includes: cleaning the substrate, drying it with high-purity nitrogen, and then preparing BiFe. 1-x Mn xO3 ferroelectric thin film layer; the specific cleaning method is as follows: the substrate is cleaned in sequence with acetone, anhydrous ethanol and deionized water, and the cleaning time for each cleaning process is 5 to 15 minutes, preferably 10 minutes.
[0077] In some embodiments, BiFe is prepared using the sol-gel method. 1-x Mn x The O3 ferroelectric thin film layer specifically includes the following steps:
[0078] Bismuth nitrate pentahydrate, ferric nitrate nonahydrate, and manganese acetate tetrahydrate were added to an organic solvent to obtain BiFe 1- x Mn x O3 precursor solution; wherein the organic solvent includes a mixture of glacial acetic acid and ethylene glycol methyl ether; the molar ratio of bismuth nitrate pentahydrate, ferric nitrate nonahydrate, and manganese acetate tetrahydrate is 1:(0.95~0.99):(0.01~0.05);
[0079] BiFe 1-x Mn x The O3 precursor solution was spin-coated onto the substrate, dried at 200–400 °C, and then annealed at 450–650 °C to obtain BiFe. 1-x Mn x O3 ferroelectric thin film layer.
[0080] Specifically, in some embodiments, BiFe was prepared using the sol-gel method. 1-x Mn x The O3 ferroelectric thin film layer specifically includes the following steps:
[0081] Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O were dissolved in an organic solvent and aged for 30–50 h to obtain BiFe 1-x Mn x O3 precursor solution; BiFe 1-x Mn x The concentration of the O3 precursor solution is 0.4–0.8 mol / L; the organic solvent includes a mixture of glacial acetic acid and ethylene glycol methyl ether; wherein the volume ratio of glacial acetic acid to ethylene glycol methyl ether is (1–3):(2–6); preferably, the volume ratio of glacial acetic acid to ethylene glycol methyl ether is 1:3; wherein, since this experiment is carried out at room temperature, and glacial acetic acid is liquid at room temperature, the volume ratio of glacial acetic acid to ethylene glycol methyl ether here refers to the volume ratio of liquid glacial acetic acid to ethylene glycol methyl ether.
[0082] BiFe 1-x Mn xThe O3 precursor solution was spin-coated onto the substrate at a speed of 3000–4000 rpm. The spin-coated wet film was dried at a temperature of 200–400°C for 5–10 min. The number of spin-coated layers was 1–5. Then, the film was annealed at a temperature of 450–650°C to obtain a BFMO ferroelectric thin film layer on the substrate surface.
[0083] Among them, BiFe 1-x Mn x The concentration of the O3 precursor solution is 0.4–0.8 mol / L, specifically: the concentration of Bi element is 0.4–0.8 mol / L, the concentration of Fe element is (0.4–0.4x)–(0.8–0.8x) mol / L, and the concentration of Mn element is (0.4x–0.8x) mol / L.
[0084] In some embodiments, the annealing time in the step of annealing at 450 to 650°C is 30 min to 1 h.
[0085] In some embodiments, the n-Ga2O3 thin film layer is prepared by pulsed laser deposition, specifically including the following steps:
[0086] Using n-Ga2O3 ceramic as the target material, BiFe was prepared. 1-x Mn x The substrate for the O3 ferroelectric thin film was placed in the vacuum chamber of a pulsed laser deposition apparatus. The substrate temperature was controlled at 25–550 °C, the pulsed laser energy at 250–600 mJ, the oxygen pressure at 0–8 Pa, and the deposition time at 20–60 min. 1-x Mn x An n-Ga2O3 thin film layer is formed by deposition on the surface of the O3 ferroelectric thin film layer.
[0087] In some embodiments, ZnO thin film layers are prepared using pulsed laser deposition, specifically including the following steps:
[0088] Using ZnO ceramic as the target material, a substrate with an n-Ga2O3 thin film layer is placed in the vacuum chamber of a pulsed laser deposition equipment. The substrate temperature is controlled at 100–600℃, the pulsed laser energy is 150–600 mJ, the oxygen pressure is 0–8 Pa, and the deposition time is 5–15 min, so that a ZnO thin film layer is deposited on the surface of the n-Ga2O3 thin film layer.
[0089] Specifically, the preparation of the top electrode using vacuum evaporation (taking Ag top electrode as an example) involves: placing the substrate with the ZnO thin film layer upside down on a square mask and then placing it in an evaporation apparatus; placing a silver wire in a tungsten boat and evacuating to 10°C. -4Pa, heat the tungsten boat, the silver wire absorbs heat and melts and then evaporates. After the Ag wire has completely evaporated, stop heating, turn off the molecular pump, and after the molecular pump speed reaches 0, turn off the mechanical pump. Open the air valve and introduce air. When the pressure in the vacuum chamber is the same as the outdoor pressure, take out the sample, and the preparation of the top electrode is completed.
[0090] Specifically, if the n-type dopant in the n-Ga2O3 thin film is Si, the preparation method of the Si-doped n-type Ga2O3 target includes the following steps:
[0091] SiO2 powder and Ga2O3 powder, weighed according to the ratio, are placed in a ball mill jar. Then, 55%–65% of the total powder mass of deionized water is added, and the mixture is ball-milled for 6–10 hours. The powder is then placed in a vacuum drying oven for drying to obtain fine powder. The specific drying temperature is 100–130℃, and the drying time is 6–12 hours. Then, 1%–5% of the total powder mass of anhydrous ethanol is added to the dried fine powder, and the mixture is ground and stirred evenly. The mixture is then pressed into ceramic blanks with a thickness of 2–5 mm under a pressure of 2–10 MPa. The ceramic blanks are then sintered at 800–1300℃ for 2–5 hours to obtain the Si-doped n-type Ga2O3 target material.
[0092] In the step of ball milling and mixing SiO2 powder and Ga2O3 powder to obtain fine powder, the molar fraction of SiO2 in the fine powder is 0.1% to 3%.
[0093] If the n-type dopant is Ge or Sn, then GeO2 powder or SnO2 powder is used instead of SiO2 powder.
[0094] The following detailed embodiments further illustrate the multi-junction self-driven deep ultraviolet photodetector and its fabrication method of this application. This section further explains the invention in conjunction with specific embodiments, but should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods, and equipment used in this invention are conventional reagents, methods, and equipment in the art.
[0095] Example 1
[0096] This application provides a ferroelectric depolarization field-enhanced multijunction photovoltaic device, specifically a ferroelectric depolarization field-enhanced multijunction photovoltaic self-driven deep ultraviolet photodetector, including:
[0097] Substrate;
[0098] BiFe 1-x Mn x An O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) is located on the substrate surface, where x = 5%, i.e., BiFe 1-x Mnx O3 has the chemical formula BiFe 0.95 Mn 0.05 O3;
[0099] n-Ga2O3 thin film layer, located in BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer away from the substrate;
[0100] The ZnO thin film layer is located on the surface of the n-Ga2O3 thin film layer away from the substrate.
[0101] The top electrode is located on the surface of the ZnO thin film layer away from the substrate;
[0102] The substrate is an FTO conductive glass substrate with a thickness of 2mm;
[0103] BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer is 230 nm;
[0104] The n-type dopant element in the n-Ga2O3 thin film is Si (i.e., it is a Si-doped n-type Ga2O3 thin film, denoted as Si:Ga2O3 thin film), the thickness of the n-Ga2O3 thin film is 120 nm, and the molar fraction of Si element in the n-Ga2O3 thin film is 0.75%.
[0105] The thickness of the ZnO thin film is 30 nm;
[0106] The top electrode is an Ag top electrode with a thickness of 30 nm.
[0107] The fabrication method of the above-mentioned multi-junction photovoltaic self-driven deep ultraviolet photodetector includes the following steps:
[0108] S1. Provide an FTO conductive glass substrate. Clean the FTO conductive glass substrate sequentially with acetone, ethanol, and deionized water for 10 min each. Then, dry it with nitrogen and immediately place it on the sample tray of a spin coater. Use a pipette to drop 30 μL of a 0.6 mol / L BFMO precursor solution onto the substrate. Set the spin coater speed and time to 500 rpm for 5 s and 4000 rpm for 15 s, respectively. Immediately after spin coating, place the substrate with the BFMO solution on a 200°C heating stage to dry for 5 min to remove moisture, then transfer it to a 400°C heating stage to dry for 5 min to remove organic matter. Repeat the spin coating and drying steps three times until the desired film thickness is achieved. Finally, anneal the substrate in a muffle furnace at 550°C for 30 min to obtain a BFMO ferroelectric thin film layer. The preparation method of the BFMO precursor solution includes the following steps:
[0109] Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O were dissolved in an organic solvent and aged for 48 h to obtain BiFe 1-x Mn x O3 precursor solution; BiFe 1-x Mn x The concentration of the O3 precursor solution was 0.6 mol / L (i.e., BiFe). 1-x Mn x The O3 precursor solution contains Bi with a concentration of 0.6 mol / L, Fe with a concentration of 0.6-0.6x mol / L, and Mn with a concentration of 0.6x mol / L; the organic solvent includes a mixture of glacial acetic acid and ethylene glycol methyl ether; wherein the molar ratio of Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O is 1:0.95:0.05; and the volume ratio of glacial acetic acid (liquid glacial acetic acid) to ethylene glycol methyl ether is 1:3.
[0110] S2. Place the sample prepared in step S1 into the vacuum chamber of the pulsed laser deposition system, then install the Si:Ga2O3 ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 550℃, oxygen is introduced to maintain the gas pressure at 1Pa throughout the film deposition process. The laser output energy is set to 300mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 20 minutes of deposition until the n-Ga2O3 film layer reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0111] The preparation method of Si:Ga2O3 ceramic target material includes the following steps:
[0112] SiO2 powder and Ga2O3 powder, weighed according to the ratio, were placed in a ball mill jar, and then 60% of the total powder mass of deionized water was added for ball milling for 9 hours. The powder was then placed in a vacuum drying oven for drying to obtain fine powder. The specific drying temperature was 120℃ and the drying time was 10 hours. Then, 4% of the total powder mass of anhydrous ethanol was added to the dried fine powder, and the mixture was ground and stirred evenly. The mixture was then pressed into a 4 mm thick ceramic blank under a pressure of 8 MPa. The ceramic blank was sintered at 1200℃ for 4 hours to obtain a Si-doped n-type Ga2O3 target, i.e., a Si:Ga2O3 ceramic target.
[0113] In the step of ball milling and mixing SiO2 powder and Ga2O3 powder to obtain fine powder, the molar fraction of SiO2 in the fine powder is 0.75%.
[0114] S3. Place the sample prepared in step S2 into the vacuum cavity of the pulsed laser deposition system, then install the ZnO ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 350℃, oxygen is introduced to maintain the gas pressure at 4Pa throughout the film deposition process. The laser output energy is set to 180mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 10 minutes of deposition until the ZnO film thickness reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0115] S4. Place the sample prepared in step S3 upside down on a square mask with dimensions of 0.5mm × 0.5mm and put it into a vapor deposition apparatus. Then, place 0.3g of silver wire in a tungsten boat and evacuate to 10°C. -4 Pa, turn on the heating, and wait for the Ag wire to evaporate completely so that the Ag top electrode reaches the required thickness to prepare the Ag top electrode.
[0116] Example 2
[0117] This application provides a ferroelectric depolarization field-enhanced multijunction photovoltaic device, specifically a ferroelectric depolarization field-enhanced multijunction photovoltaic self-driven deep ultraviolet photodetector, including:
[0118] Substrate;
[0119] BiFe 1-x Mn x An O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) is located on the substrate surface, where x = 5%, i.e., BiFe 1-x Mn x O3 has the chemical formula BiFe 0.95 Mn 0.05 O3;
[0120] n-Ga2O3 thin film layer, located in BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer away from the substrate;
[0121] The ZnO thin film layer is located on the surface of the n-Ga2O3 thin film layer away from the substrate.
[0122] The top electrode is located on the surface of the ZnO thin film layer away from the substrate;
[0123] The substrate is an FTO conductive glass substrate with a thickness of 2mm;
[0124] BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer is 230 nm;
[0125] The n-type dopant element in the n-Ga2O3 thin film is Si (i.e., it is a Si-doped n-type Ga2O3 thin film, denoted as Si:Ga2O3 thin film), the thickness of the n-Ga2O3 thin film is 150 nm, and the molar fraction of Si element in the n-Ga2O3 thin film is 0.75%.
[0126] The thickness of the ZnO thin film is 30 nm;
[0127] The top electrode is an Ag top electrode with a thickness of 30 nm.
[0128] The fabrication method of the above-mentioned multi-junction photovoltaic self-driven deep ultraviolet photodetector includes the following steps:
[0129] S1. Provide an FTO conductive glass substrate. Clean the FTO conductive glass substrate sequentially with acetone, ethanol, and deionized water for 10 min each. Then, dry it with nitrogen and immediately place it on the sample tray of a spin coater. Use a pipette to drop 30 μL of a 0.6 mol / L BFMO precursor solution onto the substrate. Set the spin coater speed and time to 500 rpm for 5 s and 4000 rpm for 15 s, respectively. Immediately after spin coating, place the substrate with the BFMO solution on a 200°C heating stage to dry for 5 min to remove moisture, then transfer it to a 400°C heating stage to dry for 5 min to remove organic matter. Repeat the spin coating and drying steps three times until the desired film thickness is achieved. Finally, anneal the substrate in a muffle furnace at 550°C for 30 min to obtain a BFMO ferroelectric thin film layer. The preparation method of the BFMO precursor solution includes the following steps:
[0130] Bi(NO3)3·5H2O, Fe(NO3)3·9H2O and Mn(C2H3O2)2·4H2O were dissolved in an organic solvent and aged for 48 h to obtain BiFe 1-x Mn x O3 precursor solution; BiFe 1-x Mn x The concentration of the O3 precursor solution was 0.6 mol / L (i.e., BiFe). 1-x Mn x The O3 precursor solution contains Bi with a concentration of 0.6 mol / L, Fe with a concentration of 0.6-0.6x mol / L, and Mn with a concentration of 0.6x mol / L; the organic solvent is a mixture of glacial acetic acid and ethylene glycol methyl ether; wherein the molar ratio of Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O is 1:0.95:0.05; and the volume ratio of glacial acetic acid (liquid glacial acetic acid) to ethylene glycol methyl ether is 1:3.
[0131] S2. Place the sample prepared in step S1 into the vacuum chamber of the pulsed laser deposition system, then install the Si:Ga2O3 ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 550℃, oxygen is introduced to maintain the gas pressure at 1Pa throughout the film deposition process. The laser output energy is set to 300mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 30 minutes of deposition until the n-Ga2O3 film layer reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0132] The preparation method of Si:Ga2O3 ceramic target material includes the following steps:
[0133] SiO2 powder and Ga2O3 powder, weighed according to the ratio, were placed in a ball mill jar, and then 60% of the total powder mass of deionized water was added for ball milling for 9 hours. The powder was then placed in a vacuum drying oven for drying to obtain fine powder. The specific drying temperature was 120℃ and the drying time was 10 hours. Then, 4% of the total powder mass of anhydrous ethanol was added to the dried fine powder, and the mixture was ground and stirred evenly. The mixture was then pressed into a 4 mm thick ceramic blank under a pressure of 8 MPa. The ceramic blank was sintered at 1200℃ for 4 hours to obtain a Si-doped n-type Ga2O3 target, i.e., a Si:Ga2O3 ceramic target.
[0134] In the step of ball milling and mixing SiO2 powder and Ga2O3 powder to obtain fine powder, the molar fraction of SiO2 in the fine powder is 0.75%.
[0135] S3. Place the sample prepared in step S2 into the vacuum cavity of the pulsed laser deposition system, then install the ZnO ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 350℃, oxygen is introduced to maintain the gas pressure at 4Pa throughout the film deposition process. The laser output energy is set to 180mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 10 minutes of deposition until the ZnO film thickness reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0136] S4. Place the sample prepared in step S3 upside down on a square mask with dimensions of 0.5mm × 0.5mm and put it into a vapor deposition apparatus. Then, place 0.3g of silver wire in a tungsten boat and evacuate to 10°C. -4 Pa, turn on heating, and wait for the Ag wire to completely evaporate so that the Ag top electrode reaches the required thickness to prepare the Ag top electrode.
[0137] Example 3
[0138] This application provides a ferroelectric depolarization field-enhanced multijunction photovoltaic device, specifically a ferroelectric depolarization field-enhanced multijunction photovoltaic self-driven deep ultraviolet photodetector, including:
[0139] Substrate;
[0140] BiFe 1-x Mn x An O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) is located on the substrate surface, where x = 5%, i.e., BiFe 1-x Mn x O3 has the chemical formula BiFe 0.95 Mn 0.05 O3;
[0141] n-Ga2O3 thin film layer, located in BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer away from the substrate;
[0142] The ZnO thin film layer is located on the surface of the n-Ga2O3 thin film layer away from the substrate.
[0143] The top electrode is located on the surface of the ZnO thin film layer away from the substrate;
[0144] The substrate is an FTO conductive glass substrate with a thickness of 2mm;
[0145] BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer is 230 nm;
[0146] The n-type dopant element in the n-Ga2O3 thin film is Si (i.e., it is a Si-doped n-type Ga2O3 thin film, denoted as Si:Ga2O3 thin film), the thickness of the n-Ga2O3 thin film is 200 nm, and the molar fraction of Si element in the n-Ga2O3 thin film is 0.75%.
[0147] The thickness of the ZnO thin film is 30 nm;
[0148] The top electrode is an Ag top electrode with a thickness of 30 nm.
[0149] The fabrication method of the above-mentioned multi-junction photovoltaic self-driven deep ultraviolet photodetector includes the following steps:
[0150] S1. Provide an FTO conductive glass substrate. Clean the FTO conductive glass substrate sequentially with acetone, ethanol, and deionized water for 10 min each. Then, dry it with nitrogen and immediately place it on the sample tray of a spin coater. Use a pipette to drop 30 μL of a 0.6 mol / L BFMO precursor solution onto the substrate. Set the spin coater speed and time to 500 rpm for 5 s and 4000 rpm for 15 s, respectively. Immediately after spin coating, place the substrate with the BFMO solution on a 200°C heating stage to dry for 5 min to remove moisture, then transfer it to a 400°C heating stage to dry for 5 min to remove organic matter. Repeat the spin coating and drying steps three times until the desired film thickness is achieved. Finally, anneal the substrate in a muffle furnace at 550°C for 30 min to obtain a BFMO ferroelectric thin film layer. The preparation method of the BFMO precursor solution includes the following steps:
[0151] Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O were dissolved in an organic solvent and aged for 48 h to obtain BiFe 1-x Mn x O3 precursor solution; BiFe 1-x Mn x The concentration of the O3 precursor solution was 0.6 mol / L (i.e., BiFe). 1-x Mn x The O3 precursor solution contains Bi with a concentration of 0.6 mol / L, Fe with a concentration of 0.6-0.6x mol / L, and Mn with a concentration of 0.6x mol / L; the organic solvent is a mixture of glacial acetic acid and ethylene glycol methyl ether; wherein the molar ratio of Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O is 1:0.95:0.05; and the volume ratio of glacial acetic acid (liquid glacial acetic acid) to ethylene glycol methyl ether is 1:3.
[0152] S2. Place the sample prepared in step S1 into the vacuum chamber of the pulsed laser deposition system, then install the Si:Ga2O3 ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 550℃, oxygen is introduced to maintain the gas pressure at 1Pa throughout the film deposition process. The laser output energy is set to 300mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 40 minutes of deposition until the n-Ga2O3 film layer reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0153] The preparation method of Si:Ga2O3 ceramic target material includes the following steps:
[0154] SiO2 powder and Ga2O3 powder, weighed according to the ratio, were placed in a ball mill jar, and then 60% of the total powder mass of deionized water was added for ball milling for 9 hours. The powder was then placed in a vacuum drying oven for drying to obtain fine powder. The specific drying temperature was 120℃ and the drying time was 10 hours. Then, 4% of the total powder mass of anhydrous ethanol was added to the dried fine powder, and the mixture was ground and stirred evenly. The mixture was then pressed into a 4 mm thick ceramic blank under a pressure of 8 MPa. The ceramic blank was sintered at 1200℃ for 4 hours to obtain a Si-doped n-type Ga2O3 target, i.e., a Si:Ga2O3 ceramic target.
[0155] In the step of ball milling and mixing SiO2 powder and Ga2O3 powder to obtain fine powder, the molar fraction of SiO2 in the fine powder is 0.75%.
[0156] S3. Place the sample prepared in step S2 into the vacuum cavity of the pulsed laser deposition system, then install the ZnO ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 350℃, oxygen is introduced to maintain the gas pressure at 4Pa throughout the film deposition process. The laser output energy is set to 180mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 10 minutes of deposition until the ZnO film thickness reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0157] S4. Place the sample prepared in step S3 upside down on a square mask with dimensions of 0.5mm × 0.5mm and put it into a vapor deposition apparatus. Then, place 0.3g of silver wire in a tungsten boat and evacuate to 10°C. -4 Pa, turn on heating, and wait for the Ag wire to completely evaporate so that the Ag top electrode reaches the required thickness to prepare the Ag top electrode.
[0158] Example 4
[0159] This application provides a ferroelectric depolarization field-enhanced multijunction photovoltaic device, specifically a ferroelectric depolarization field-enhanced multijunction photovoltaic self-driven deep ultraviolet photodetector, including:
[0160] Substrate;
[0161] BiFe 1-x Mn x An O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) is located on the substrate surface, where x = 5%, i.e., BiFe 1-x Mn x O3 has the chemical formula BiFe 0.95 Mn 0.05 O3;
[0162] n-Ga2O3 thin film layer, located in BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer away from the substrate;
[0163] The ZnO thin film layer is located on the surface of the n-Ga2O3 thin film layer away from the substrate.
[0164] The top electrode is located on the surface of the ZnO thin film layer away from the substrate;
[0165] The substrate is an FTO conductive glass substrate with a thickness of 2mm;
[0166] BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer is 230 nm;
[0167] The n-type dopant element in the n-Ga2O3 thin film is Si (i.e., it is a Si-doped n-type Ga2O3 thin film, denoted as Si:Ga2O3 thin film), the thickness of the n-Ga2O3 thin film is 240 nm, and the molar fraction of Si element in the n-Ga2O3 thin film is 0.75%.
[0168] The thickness of the ZnO thin film is 30 nm;
[0169] The top electrode is an Ag top electrode with a thickness of 30 nm;
[0170] The aforementioned multi-junction self-driven deep ultraviolet photodetector is a ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector.
[0171] The fabrication method of the above-mentioned multi-junction self-driven deep ultraviolet photodetector includes the following steps:
[0172] S1. Provide an FTO conductive glass substrate. Clean the FTO conductive glass substrate sequentially with acetone, ethanol, and deionized water for 10 min each. Then, dry it with nitrogen and immediately place it on the sample tray of a spin coater. Use a pipette to drop 30 μL of a 0.6 mol / L BFMO precursor solution onto the substrate. Set the spin coater speed and time to 500 rpm for 5 s and 4000 rpm for 15 s, respectively. Immediately after spin coating, place the substrate with the BFMO solution on a 200°C heating stage to dry for 5 min to remove moisture, then transfer it to a 400°C heating stage to dry for 5 min to remove organic matter. Repeat the spin coating and drying steps three times until the desired film thickness is achieved. Finally, anneal the substrate in a muffle furnace at 550°C for 30 min to obtain a BFMO ferroelectric thin film layer. The preparation method of the BFMO precursor solution includes the following steps:
[0173] Bi(NO3)3·5H2O, Fe(NO3)3·9H2O and Mn(C2H3O2)2·4H2O were dissolved in an organic solvent and aged for 48 h to obtain BiFe 1-x Mn x O3 precursor solution; BiFe 1-x Mn x The concentration of the O3 precursor solution was 0.6 mol / L (i.e., BiFe). 1-x Mn x The O3 precursor solution contains Bi with a concentration of 0.6 mol / L, Fe with a concentration of 0.6-0.6x mol / L, and Mn with a concentration of 0.6x mol / L; the organic solvent is a mixture of glacial acetic acid and ethylene glycol methyl ether; wherein the molar ratio of Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O is 1:0.95:0.05; and the volume ratio of glacial acetic acid (liquid glacial acetic acid) to ethylene glycol methyl ether is 1:3.
[0174] S2. Place the sample prepared in step S1 into the vacuum chamber of the pulsed laser deposition system, then install the Si:Ga2O3 ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 550℃, oxygen is introduced to maintain the gas pressure at 1Pa throughout the film deposition process. The laser output energy is set to 300mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 50 minutes of deposition until the n-Ga2O3 film layer reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0175] The preparation method of Si:Ga2O3 ceramic target material includes the following steps:
[0176] SiO2 powder and Ga2O3 powder, weighed according to the ratio, were placed in a ball mill jar, and then 60% of the total powder mass of deionized water was added for ball milling for 9 hours. The powder was then placed in a vacuum drying oven for drying to obtain fine powder. The specific drying temperature was 120℃ and the drying time was 10 hours. Then, 4% of the total powder mass of anhydrous ethanol was added to the dried fine powder, and the mixture was ground and stirred evenly. The mixture was then pressed into a 4 mm thick ceramic blank under a pressure of 8 MPa. The ceramic blank was sintered at 1200℃ for 4 hours to obtain a Si-doped n-type Ga2O3 target, i.e., a Si:Ga2O3 ceramic target.
[0177] In the step of ball milling and mixing SiO2 powder and Ga2O3 powder to obtain fine powder, the molar fraction of SiO2 in the fine powder is 0.75%.
[0178] S3. Place the sample prepared in step S2 into the vacuum cavity of the pulsed laser deposition system, then install the ZnO ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 350℃, oxygen is introduced to maintain the gas pressure at 4Pa throughout the film deposition process. The laser output energy is set to 180mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 10 minutes of deposition until the ZnO film thickness reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0179] S4. Place the sample prepared in step S3 upside down on a square mask with dimensions of 0.5mm × 0.5mm and put it into a vapor deposition apparatus. Then, place 0.3g of silver wire in a tungsten boat and evacuate to 10°C. -4 Pa, turn on the heating, and wait for the Ag wire to evaporate completely so that the Ag top electrode reaches the required thickness to prepare the Ag top electrode.
[0180] Example 5
[0181] This application provides a ferroelectric depolarization field-enhanced multijunction photovoltaic device, specifically a ferroelectric depolarization field-enhanced multijunction photovoltaic self-driven deep ultraviolet photodetector, including:
[0182] Substrate;
[0183] BiFe 1-x Mn x An O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) is located on the substrate surface, where x = 5%, i.e., BiFe 1-x Mn x O3 has the chemical formula BiFe 0.95 Mn 0.05 O3;
[0184] n-Ga2O3 thin film layer, located in BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer away from the substrate;
[0185] The ZnO thin film layer is located on the surface of the n-Ga2O3 thin film layer away from the substrate.
[0186] The top electrode is located on the surface of the ZnO thin film layer away from the substrate;
[0187] The substrate is an FTO conductive glass substrate with a thickness of 2mm;
[0188] BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer is 230 nm;
[0189] The n-type dopant element in the n-Ga2O3 thin film is Si (i.e., it is a Si-doped n-type Ga2O3 thin film, denoted as Si:Ga2O3 thin film), the thickness of the n-Ga2O3 thin film is 300 nm, and the molar fraction of Si element in the n-Ga2O3 thin film is 0.75%.
[0190] The thickness of the ZnO thin film is 30 nm;
[0191] The top electrode is an Ag top electrode with a thickness of 30 nm;
[0192] The aforementioned multi-junction self-driven deep ultraviolet photodetector is a ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector.
[0193] The fabrication method of the above-mentioned multi-junction self-driven deep ultraviolet photodetector includes the following steps:
[0194] S1. Provide an FTO conductive glass substrate. Clean the FTO conductive glass substrate sequentially with acetone, ethanol, and deionized water for 10 min each. Then, dry it with nitrogen and immediately place it on the sample tray of a spin coater. Use a pipette to drop 30 μL of a 0.6 mol / L BFMO precursor solution onto the substrate. Set the spin coater speed and time to 500 rpm for 5 s and 4000 rpm for 15 s, respectively. Immediately after spin coating, place the substrate with the BFMO solution on a 200°C heating stage to dry for 5 min to remove moisture, then transfer it to a 400°C heating stage to dry for 5 min to remove organic matter. Repeat the spin coating and drying steps three times until the desired film thickness is achieved. Finally, anneal the substrate in a muffle furnace at 550°C for 30 min to obtain a BFMO ferroelectric thin film layer. The preparation method of the BFMO precursor solution includes the following steps:
[0195] Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O were dissolved in an organic solvent and aged for 48 h to obtain BiFe 1-x Mn x O3 precursor solution; BiFe 1-x Mn x The concentration of the O3 precursor solution was 0.6 mol / L (i.e., BiFe). 1-x Mn xThe O3 precursor solution contains Bi with a concentration of 0.6 mol / L, Fe with a concentration of 0.6-0.6x mol / L, and Mn with a concentration of 0.6x mol / L; the organic solvent is a mixture of glacial acetic acid and ethylene glycol methyl ether; wherein the molar ratio of Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O is 1:0.95:0.05; and the volume ratio of glacial acetic acid (liquid glacial acetic acid) to ethylene glycol methyl ether is 1:3.
[0196] S2. Place the sample prepared in step S1 into the vacuum chamber of the pulsed laser deposition system, then install the Si:Ga2O3 ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 550℃, oxygen is introduced to maintain the gas pressure at 1Pa throughout the film deposition process. The laser output energy is set to 300mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 60 minutes of deposition until the n-Ga2O3 film layer reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0197] The preparation method of Si:Ga2O3 ceramic target material includes the following steps:
[0198] SiO2 powder and Ga2O3 powder, weighed according to the ratio, were placed in a ball mill jar, and then 60% of the total powder mass of deionized water was added for ball milling for 9 hours. The powder was then placed in a vacuum drying oven for drying to obtain fine powder. The specific drying temperature was 120℃ and the drying time was 10 hours. Then, 4% of the total powder mass of anhydrous ethanol was added to the dried fine powder, and the mixture was ground and stirred evenly. The mixture was then pressed into a 4 mm thick ceramic blank under a pressure of 8 MPa. The ceramic blank was sintered at 1200℃ for 4 hours to obtain a Si-doped n-type Ga2O3 target, i.e., a Si:Ga2O3 ceramic target.
[0199] In the step of ball milling and mixing SiO2 powder and Ga2O3 powder to obtain fine powder, the molar fraction of SiO2 in the fine powder is 0.75%.
[0200] S3. Place the sample prepared in step S2 into the vacuum cavity of the pulsed laser deposition system, then install the ZnO ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 350℃, oxygen is introduced to maintain the gas pressure at 4Pa throughout the film deposition process. The laser output energy is set to 180mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 10 minutes of deposition until the ZnO film thickness reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0201] S4. Place the sample prepared in step S3 upside down on a square mask with dimensions of 0.5mm × 0.5mm and put it into a vapor deposition apparatus. Then, place 0.3g of silver wire in a tungsten boat and evacuate to 10°C. -4 Pa, turn on the heating, and wait for the Ag wire to evaporate completely so that the Ag top electrode reaches the required thickness to prepare the Ag top electrode.
[0202] Comparative Example 1
[0203] This comparative example provides a Si:Ga2O3-based self-driven deep ultraviolet photodetector, comprising:
[0204] Substrate;
[0205] An n-Ga2O3 thin film layer is located on the substrate surface;
[0206] The top electrode is located on the surface of the n-Ga2O3 thin film layer away from the substrate.
[0207] The substrate is an FTO conductive glass substrate with a thickness of 2mm;
[0208] The n-type dopant element in the n-Ga2O3 thin film is Si (i.e., it is a Si-doped n-type Ga2O3 thin film, denoted as Si:Ga2O3 thin film), the thickness of the n-Ga2O3 thin film is 200 nm, and the molar fraction of Si element in the n-Ga2O3 thin film is 0.75%.
[0209] The top electrode is an Ag top electrode with a thickness of 30 nm.
[0210] The above-mentioned method for fabricating a Si:Ga2O3-based self-driven deep ultraviolet photodetector includes the following steps:
[0211] S1. Provide an FTO conductive glass substrate. Clean the FTO conductive glass substrate sequentially with acetone, ethanol, and deionized water for 10 minutes each. Then, dry it with nitrogen and immediately place it in the vacuum chamber of the pulsed laser deposition system. Then, install the Si:Ga2O3 ceramic target and evacuate to 10°C. -4 Pa;
[0212] The preparation method of Si:Ga2O3 ceramic target material includes the following steps:
[0213] SiO2 powder and Ga2O3 powder, weighed according to the ratio, were placed in a ball mill jar, and then 60% of the total powder mass of deionized water was added for ball milling for 9 hours. The powder was then placed in a vacuum drying oven for drying to obtain fine powder. The specific drying temperature was 120℃ and the drying time was 10 hours. Then, 4% of the total powder mass of anhydrous ethanol was added to the dried fine powder, and the mixture was ground and stirred evenly. The mixture was then pressed into a 4 mm thick ceramic blank under a pressure of 8 MPa. The ceramic blank was sintered at 1200℃ for 4 hours to obtain a Si-doped n-type Ga2O3 target, i.e., a Si:Ga2O3 ceramic target.
[0214] In the step of ball milling and mixing SiO2 powder and Ga2O3 powder to obtain fine powder, the molar fraction of SiO2 in the fine powder is 0.75%.
[0215] S2. After the substrate temperature is raised to 550℃, oxygen is introduced to maintain the gas pressure at 4Pa throughout the film deposition process. The laser output energy is set to 300mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 40 minutes of deposition until the n-Ga2O3 film layer reaches the required thickness, oxygen introduction and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0216] S3. Place the sample prepared in step S2 upside down on a square mask with dimensions of 0.5mm × 0.5mm and put it into a vapor deposition apparatus. Then, place 0.3g of silver wire in a tungsten boat and evacuate to 10°C. -4 Pa, turn on the heating, and wait for the Ag wire to evaporate completely so that the Ag top electrode reaches the required thickness to prepare the Ag top electrode.
[0217] Comparative Example 2
[0218] This comparative example provides a ferroelectric depolarization field-enhanced BFMO / Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector, including:
[0219] Substrate;
[0220] BiFe 1-x Mn x An O3 ferroelectric thin film layer (denoted as BFMO ferroelectric thin film layer) is located on the substrate surface, where x = 5%, i.e., BiFe 1-x Mn x O3 has the chemical formula BiFe 0.95 Mn 0.05 O3;
[0221] Ga2O3 thin film layer, located in BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer away from the substrate;
[0222] The ZnO thin film layer is located on the surface of the n-Ga2O3 thin film layer away from the substrate.
[0223] The top electrode is located on the surface of the ZnO thin film layer away from the substrate;
[0224] The substrate is an FTO conductive glass substrate with a thickness of 2mm;
[0225] BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer is 230 nm;
[0226] The thickness of the Ga2O3 thin film is 300 nm;
[0227] The thickness of the ZnO thin film is 30 nm;
[0228] The top electrode is an Ag top electrode with a thickness of 30 nm;
[0229] The fabrication method of the above-mentioned ferroelectric depolarization field-enhanced BFMO / Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector includes the following steps:
[0230] S1. Provide an FTO conductive glass substrate. Clean the FTO conductive glass substrate sequentially with acetone, ethanol, and deionized water for 10 min each. Then, dry it with nitrogen and immediately place it on the sample tray of a spin coater. Use a pipette to drop 30 μL of a 0.6 mol / L BFMO precursor solution onto the substrate. Set the spin coater speed and time to 500 rpm for 5 s and 4000 rpm for 15 s, respectively. Immediately after spin coating, place the substrate with the BFMO solution on a 200°C heating stage to dry for 5 min to remove moisture, then transfer it to a 400°C heating stage to dry for 5 min to remove organic matter. Repeat the spin coating and drying steps three times until the desired film thickness is achieved. Finally, anneal the substrate in a muffle furnace at 550°C for 30 min to obtain a BFMO ferroelectric thin film layer. The preparation method of the BFMO precursor solution includes the following steps:
[0231] Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O were dissolved in an organic solvent and aged for 48 h to obtain BiFe 1-x Mn x O3 precursor solution; BiFe 1-x Mn x The concentration of the O3 precursor solution was 0.6 mol / L (i.e., BiFe). 1-x Mn xThe O3 precursor solution contains Bi with a concentration of 0.6 mol / L, Fe with a concentration of 0.6-0.6x mol / L, and Mn with a concentration of 0.6x mol / L; the organic solvent is a mixture of glacial acetic acid and ethylene glycol methyl ether; wherein the molar ratio of Bi(NO3)3·5H2O, Fe(NO3)3·9H2O, and Mn(C2H3O2)2·4H2O is 1:0.95:0.05; and the volume ratio of glacial acetic acid (liquid glacial acetic acid) to ethylene glycol methyl ether is 1:3.
[0232] S2. Place the sample prepared in step S1 into the vacuum chamber of the pulsed laser deposition system, then install the Ga2O3 ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 550℃, oxygen is introduced to maintain the gas pressure at 1Pa throughout the film deposition process. The laser output energy is set to 300mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 30 minutes of deposition until the Ga2O3 film layer reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0233] S3. Place the sample prepared in step S2 into the vacuum cavity of the pulsed laser deposition system, then install the ZnO ceramic target and evacuate to 10°C. -4 Pa; After the substrate temperature is raised to 350℃, oxygen is introduced to maintain the gas pressure at 4Pa throughout the film deposition process. The laser output energy is set to 180mJ and the pulse frequency is 5Hz. Then the laser is turned on to start film deposition. After 10 minutes of deposition until the ZnO film thickness reaches the required thickness, oxygen supply and heating are stopped. The sample is taken out after it cools naturally to room temperature.
[0234] S4. Place the sample prepared in step S3 upside down on a square mask with dimensions of 0.5mm × 0.5mm and put it into a vapor deposition apparatus. Then, place 0.3g of silver wire in a tungsten boat and evacuate to 10°C. -4 Pa, turn on heating, and wait for the Ag wire to completely evaporate so that the Ag top electrode reaches the required thickness to prepare the Ag top electrode.
[0235] Performance testing
[0236] The photocurrent response spectra of the ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetectors prepared in Examples 1-5 under 275nm ultraviolet light illumination were tested, and the results are as follows: Figure 2 As shown.
[0237] from Figure 2As can be seen, with the increase of the Si:Ga2O3 layer thickness in the device, the photocurrent response of the device first increases and then decreases. Among them, the device prepared in Example 3 has the largest photocurrent response of 22.8 nA.
[0238] The spectral responsivity curves of the ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetectors prepared in Examples 1-5 are shown in the figure. Figure 3 As shown.
[0239] from Figure 3 As can be seen, with the increase of the Si:Ga2O3 layer thickness in the device, the peak response wavelength of the device gradually red-shifts (from 245nm to 260nm), and the peak responsivity shows a trend of first increasing and then decreasing. Among them, the device prepared in Example 3 has the largest peak responsivity, with a peak responsivity of 46.6mA / W at 260nm (46.6mA / W@260nm).
[0240] The detectivity curves of the ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetectors prepared in Examples 1-5 are shown in the figure. Figure 4 As shown.
[0241] from Figure 4 As can be seen, with the increase of the Si:Ga2O3 layer thickness in the device, the detector efficiency first increases and then decreases. Among them, the device prepared in Example 3 has the highest detector efficiency, which is 1.02 × 10⁻⁶ at 260 nm. 12 Jones (1.02×10 12 Jones@260nm).
[0242] The single-cycle It curve of the ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetector prepared in Example 3 under 260nm ultraviolet light irradiation was tested, and the results are as follows: Figure 5 As shown.
[0243] from Figure 5 As can be seen from this, the rise time of the device ( Figure 5 Middle τ r ) and descent response time ( Figure 5 Middle τ d The times were 8.3ms and 14.4ms, respectively.
[0244] The photocurrent response spectra of the ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetector prepared in Example 3 under different polarization states under 260nm ultraviolet light illumination were tested. The results are as follows: Figure 6 As shown.
[0245] from Figure 6 As can be seen, the device exhibits a strong photocurrent response to 260nm monochromatic light, with photocurrent responses of 1.79nA, 1.64nA, and 1.55nA in the upward polarization, unpolarized, and downward polarization states, respectively.
[0246] The spectral responsivity curves of the ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetector prepared in Example 3 under different polarization states are shown in the figure below. Figure 7 As shown.
[0247] from Figure 7 As can be seen, the peak responsivity of the device in the upward polarization, unpolarized, and downward polarization states are 50.8 mA / W, 46.6 mA / W, and 44.0 mA / W, respectively, indicating that the device has higher performance in the upward polarization state.
[0248] The single-cycle It curves of the Si:Ga2O3-based self-driven deep ultraviolet photodetector prepared in Comparative Example 1 and the ferroelectric depolarization field-enhanced BFMO / Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Comparative Example 2 were tested, and the results are as follows: Figure 8 As shown.
[0249] from Figure 8 As can be seen, the rise time and fall time (under 245nm UV irradiation) of the Si:Ga2O3-based self-driven deep ultraviolet photodetector prepared in Comparative Example 1 are 26ms and 26ms, respectively. The rise time and fall time (under 270nm UV irradiation) of the ferroelectric depolarization field-enhanced BFMO / Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Comparative Example 2 are 360ms and 86ms, respectively. The response speed of the devices prepared in Comparative Examples 1 and 2 is significantly slower than that of the ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Example 3.
[0250] The spectral responsivity curves of the ferroelectric depolarization field-enhanced BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetector prepared in Example 3, the Si:Ga2O3-based self-driven deep ultraviolet photodetector prepared in Comparative Example 1, and the ferroelectric depolarization field-enhanced BFMO / Ga2O3 / ZnO multijunction self-driven deep ultraviolet photodetector prepared in Comparative Example 2 are shown in the figure. Figure 9 As shown.
[0251] from Figure 9 As can be seen, the peak response wavelength of the photodetector prepared in Comparative Example 1 is located at 235 nm, while the peak response wavelengths of the photodetectors prepared in Comparative Example 2 and Example 3 are both at 260 nm. Among them, the responsivity (46.6 mA / W) of the ferroelectric depolarization field enhanced BFMO / Si:Ga2O3 / ZnO multijunction photovoltaic self-driven deep ultraviolet photodetector prepared in Example 3 is significantly higher than that of the Si:Ga2O3-based self-driven deep ultraviolet photodetector prepared in Comparative Example 1 (12.5 mA / W). This is because the detector in Example 3 utilizes the built-in electric field at the interface of the BFMO / n-Ga2O3 and n-Ga2O3 / ZnO heterojunction and the iron inside the BFMO... The depolarization field is used to jointly separate photogenerated carriers. The responsivity (46.6 mA / W) of the BFMO / n-Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Example 3 is also higher than that of the BFMO / Ga2O3 / ZnO multi-junction self-driven deep ultraviolet photodetector prepared in Comparative Example 2 (25.1 mA / W). This is because the carrier concentration of the functional layer (Ga2O3) is appropriately increased by n-type doping, thereby improving the transmission efficiency of photogenerated carriers.
[0252] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A ferroelectric depolarization field-enhanced multijunction photovoltaic device, characterized in that, include: Substrate; BiFe 1-x Mn x An O3 ferroelectric thin film layer is located on the surface of the substrate, wherein 1% ≤ x ≤ 5%; n-Ga2O3 thin film layer, located in the BiFe 1-x Mn x The surface of the O3 ferroelectric thin film layer away from the substrate; A ZnO thin film layer is located on the surface of the n-Ga2O3 thin film layer on the side away from the substrate; The top electrode is located on the surface of the ZnO thin film layer away from the substrate; The substrate includes either an FTO conductive glass substrate or an ITO conductive glass substrate. The ferroelectric depolarization field-enhanced multijunction photovoltaic device is a ferroelectric depolarization field-enhanced multijunction photovoltaic self-driven deep ultraviolet photodetector. BiFe 1-x Mn x The O3 ferroelectric thin film layer is designated as the BFMO ferroelectric thin film layer. By adjusting the direction of the ferroelectric depolarization electric field in the BFMO ferroelectric thin film layer to be consistent with the direction of the built-in electric field at the interface of BFMO / n-Ga2O3 heterojunction and n-Ga2O3 / ZnO heterojunction, the three electric fields in the same direction can be used to separate photogenerated carriers.
2. The ferroelectric depolarization field-enhanced multijunction photovoltaic device as described in claim 1, characterized in that, The n-type doping element in the n-Ga2O3 thin film layer includes at least one of Si, Ge, and Sn; The molar fraction of n-type doped elements in the n-Ga2O3 thin film layer is 0.1% to 3%.
3. The ferroelectric depolarization field-enhanced multijunction photovoltaic device as described in claim 1, characterized in that, The top electrode includes any one of Ag electrode, Au electrode, In electrode, and ITO electrode.
4. The ferroelectric depolarization field-enhanced multijunction photovoltaic device as described in any one of claims 1 to 3, characterized in that, The BiFe 1-x Mn x The thickness of the O3 ferroelectric thin film layer is 80~400 nm; And / or, the thickness of the n-Ga2O3 thin film layer is 120~300 nm; And / or, the thickness of the ZnO thin film layer is 10~50 nm.
5. A method for fabricating a ferroelectric depolarization field-enhanced multijunction photovoltaic device as described in any one of claims 1 to 4, characterized in that, Includes the following steps: Provide substrate; BiFe was prepared on the substrate surface 1-x Mn x O3 ferroelectric thin film layer; In the BiFe 1-x Mn x An n-Ga2O3 thin film layer is prepared on the surface of the O3 ferroelectric thin film layer away from the substrate; A ZnO thin film layer is prepared on the surface of the n-Ga2O3 thin film layer away from the substrate; A top electrode is fabricated on the surface of the ZnO thin film layer away from the substrate.
6. The method for fabricating a ferroelectric depolarization field-enhanced multijunction photovoltaic device as described in claim 5, characterized in that, BiFe was prepared on the substrate surface using pulsed laser deposition, magnetron sputtering, or sol-gel methods. 1-x Mn x O3 ferroelectric thin film layer; Atomic layer deposition, magnetron sputtering, pulsed laser deposition, or sol-gel method can be used to deposit BiFe 1-x Mn x n-Ga2O3 thin film layer is prepared on the surface of O3 ferroelectric thin film layer; ZnO thin films were prepared on the surface of the n-Ga2O3 thin film using atomic layer deposition, magnetron sputtering, or pulsed laser deposition. Top electrodes are prepared on the surface of the ZnO thin film using vacuum evaporation, magnetron sputtering, or electron beam deposition.
7. The method for fabricating a ferroelectric depolarization field-enhanced multijunction photovoltaic device as described in claim 6, characterized in that, BiFe was prepared by sol-gel method 1-x Mn x The O3 ferroelectric thin film layer specifically includes the following steps: Bismuth nitrate pentahydrate, ferric nitrate nonahydrate, and manganese acetate tetrahydrate were added to an organic solvent to obtain BiFe 1-x Mn x O3 precursor solution; wherein the organic solvent includes a mixture of glacial acetic acid and ethylene glycol methyl ether; the molar ratio of bismuth nitrate pentahydrate, ferric nitrate nonahydrate, and manganese acetate tetrahydrate is 1:(0.95~0.99):(0.01~0.05); BiFe 1-x Mn x The O3 precursor solution was spin-coated onto the substrate, dried at 200–400°C, and then annealed at 450–650°C to obtain BiFe. 1-x Mn x O3 ferroelectric thin film layer.
8. The method for fabricating a ferroelectric depolarization field-enhanced multijunction photovoltaic device as described in claim 6, characterized in that, The n-Ga2O3 thin film layer was prepared by pulsed laser deposition, specifically including the following steps: Using n-Ga2O3 ceramic as the target material, BiFe was prepared. 1-x Mn x The O3 ferroelectric thin film substrate was placed in the vacuum chamber of a pulsed laser deposition apparatus. The substrate temperature was controlled at 25–550°C, the pulsed laser energy at 250–600 mJ, the oxygen pressure at 0–8 Pa, and the deposition time at 20–60 min. 1-x Mn x An n-Ga2O3 thin film layer is formed by deposition on the surface of the O3 ferroelectric thin film layer.
9. The method for fabricating a ferroelectric depolarization field-enhanced multijunction photovoltaic device as described in claim 6, characterized in that, The ZnO thin film layer is prepared by pulsed laser deposition, specifically including the following steps: Using ZnO ceramic as the target material, a substrate with an n-Ga2O3 thin film layer is placed in the vacuum chamber of a pulsed laser deposition equipment. The substrate temperature is controlled at 100~600°C, the pulsed laser energy is 150~600 mJ, the oxygen pressure is 0~8 Pa, and the deposition time is 5~15 min, so that a ZnO thin film layer is deposited on the surface of the n-Ga2O3 thin film layer.
Citation Information
Patent Citations
Ferroelectric-semiconductor pn junction type novel laminated solar cell
CN105390564A
Ferroelectric-semiconductor quantum dot coupling enhanced solar cell and preparation method thereof
CN114141892A